Implementasi Model Pembelajaran Number Head Together Terhadap Kemandirian Belajar Matematis Siswa - Siregar, R. Maisaroh Rezyekiyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to analyze the impact of implementing the Number Head Together (NHT) cooperative learning model on students' independent mathematical learning. The urgency of this research is based on the low level of student learning independence, especially in learning mathematics, which is often considered difficult and confusing. To overcome this problem, a learning approach is needed that is able to increase students' initiative, responsibility and self-confidence in learning. This research uses a literature review method by analyzing seven relevant research articles. The selected articles contain empirical findings about the effectiveness of the NHT model in increasing students' learning independence and mathematical learning outcomes. The results of the analysis show that the NHT model is successful in increasing student learning independence through a cooperative learning structure that encourages active interaction and a sense of responsibility within the group. Increased learning independence also has an impact on improving students' critical thinking skills, problem solving, and understanding of mathematical concepts. Apart from that, this model has been proven to be able to increase students' motivation to learn independently and actively. The implication of the results of this research is that the NHT cooperative learning model can be used as an alternative teaching strategy for educators, especially in subjects that require in-depth understanding of concepts such as mathematics. The application of this model not only supports improving student learning outcomes, but also develops important non-academic skills, such as the ability to work together and independence. This research makes a significant contribution to the educational literature and innovative teaching practices.